Swedish National Celiac Disease Register - Ivarsson, Anneli (Umeå University, 2020)
Celiac disease, also known as gluten intolerance, is a permanent sensitivity to gluten which is found in wheat, rye and barley. The cause of celiac disease is still unclear but we know that both heredity and environment play a role. In Sweden, celiac disease more common than in many other countries. It is crucial to find out why this is so and if we can reduce the incidence of celiac disease by changing lifestyle in any way. We can increase the awareness of celiac disease by following the pattern of the disease across the country as well as through other research.

Since 1998 Sweden has had a unique incidence register for celiac disease in Sweden. The register was started through the initiative of the Swedish Pediatric Association (Barnläkarföreingen/BLF). In 1996 the Board offered new guidance on the introduction of gluten to the infant diet and the registry is an important part of quality assurance related to this.

The registry is administered, via the BLF's Gastroenterology and Nutrition section and, at the Department of Epidemiology and Gublic Health, Umeå University. This includes, among other things, planning and ongoing work with the registry to regularly send back reports to the participating units and to compile the incidence trends. The register’s steering group consists of three pediatricians; one representative of the Section’s Board, the celiac disease working group on celiac disease, and the registry management.

The registry has ethical approval and complies with the Personal Data Act and privacy regulations. Under this Act, children and parents have the right to obtain extracts from the register.

Purpose:

Through a nationwide registry for celiac disease in Swedish children the trend of the incidence of celiac disease can be followed and changes over time and geographical differences can be analyzed. The registry shall form the basis of other studies, for example disease etiology, opportunities for prevention, diagnosis, and long-term consequences with a goal to providing greater knowledge about celiac disease.

Celiaki, även känt som glutenintolerans, är en permanent känslighet för gluten som finns i vete, råg och korn. Orsaken till celiaki är fortfarande oklar men man vet att både arv och miljö har betydelse. I Sverige är celiaki vanligare än i många andra länder. Det är viktigt att ta reda på varför det är så och om förekomsten av celiaki kan minska genom ändrad livsstil. Genom att följa utvecklingen av sjukdomen i hela landet, och genom annan forskning, kan medvetenheten om celiaki öka.

Sedan 1998 finns i Sverige ett unikt incidensregister för celiaki i Sverige. Registret startades på initiativ av Barnläkarföreningen (BLF). Styrelsen gav 1996 ut nya rekommendationer för introduktion av gluten i spädbarnskosten och registret är en viktig del av den kvalitetssäkringen som då efterlystes.

Uppdraget att administrera registret har, via BLF’s sektion för gastroenterologi och nutrition, lämnats till Institutionen för Epidemiologi och Folkhälsovetenskap vid Umeå Universitet. I detta ingår planering och det fortlöpande arbetet med registret, bl a att regelbundet skicka återrapporter till deltagande enheter och sammanställning av incidensutvecklingen. Registrets styrgrupp består av tre barnläkare; en representant vardera för sektionens styrelse, arbetsgruppen för celiaki och registrets administration .

Registret har etiskt godkännande och följer personuppgiftlagen samt föreskrifter om sekretess. Barn och föräldrar har enligt datalagen rätt att få utdrag ur registret.

Syfte:

Att genom ett rikstäckande register för celiaki hos svenska barn följa utvecklingen av incidensen och analysera till exempel förändringar över tid och geografiska skillnader. Vidare är syftet att registret skall utgöra bas för andra studier om till exempel etiologi, möjligheter till prevention, diagnostik, konsekvenser på sikt med syfte att ge ökad kunskap om celiaki.
Swedish National Celiac Disease Register
Keywords: Primary Prevention; Primärprevention; Registries; Register; Celiac Disease; Glutenintolerans; Glutens; Gluten; celiac; celiaki; wheat; vete; rye; råg; grain; korn; national register; nationellt register; infant feeding recommendations; rekommenderad spädbarnskost; Swedish Pediatric Association; Svenska Barnläkarföreningen; nutrition; nutrition; HEALTH; HÄLSA; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Medical and Health Sciences; Medicin och hälsovetenskap; Basic Medicine; Medicinska och farmaceutiska grundvetenskaper; Gastroenterology and Hepatology; Gastroenterologi och hepatologi; Diet and nutrition; Kost och näring; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin